THE INCIDENCE OF PHLEBITIS AMONG INPATIENT IN THE HOSPITAL: SYSTEMATIC REVIEW - Muchamad Muchamad; Mieke Savitri (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: Plebitis causes increase in medical cost and decreasing motivation in health workers and patients. One of the important issues in phlebitis can be found in the treatment process and has a great risk for the occurrence of a complication that can cause thrombus which subsequently becomes thrombophlebitis, causing the need to increase infuse therapy Methods: Eligible studies for this systematic review constitute results that summarize influence factors related causes plebitis. We systematically searched ProQuest, Springer, Google Scholar from 7 days on 23-30 April 2018 for eligible systematic reviews with language limitation in English and Indonesian. Results: The literature search and screening process resulted in 21 full text articles. We found all 21 studies results proved influence factors that can cause plebitis and can be categorizes to 4 major factor which are: procedure and techniques,place and position,people,and types of fluids and medicines factors. Influence factors that mostly cause plebitis occurring in the 7 countries are from procedures and techniques, and people factors. Many are caused by violation the procedures and low soft skill in health workers. Conclusions: Plebitis incidence has become major issue in nosocomial infection at the hospital many countries. There should be new policy for monitoring and evaluation, supervision, documentation, analysis in plebitis sign with patient condition, increased competence knowledge and soft skill of health workers, fluid analysis and medicines, and nurse compliance for implementation of procedures and protocol. Plebitis is of particular concern because it can hurt many sectors ranging from patient, hospital, government and countries. It can cause increased length of hospital stay, increased medical cost and decreased motivation of work.